Persons with Epilepsy: Between Social Inclusion and Marginalisation - Simona Mlinar; Davorina Petek; Živa Cotič; Metka Mencin Čeplak; Marjan Zaletel (Behavioural Neurology)
Background. Epilepsy is a chronic neurological disorder that can lead to complex psychosocial consequences. Epilepsy can change the social status of persons with epilepsy (PWE) and has an effect on their social inclusion as well as their perception of social inclusion. This study aims to explore subjective experiences with social inclusion of PWE in Slovenia. Methods. This study takes a qualitative approach. Eleven semistructured interviews were conducted with eleven participants. Interviews were analysed using thematic analysis. Results. Epilepsy has physical, emotional, and social consequences. Physical consequences of epilepsy are mainly tiredness and exhaustion following an epileptic episode, frequently accompanied by headaches. Emotional consequences are different forms of fear. The main social consequence identified is a negative effect on PWE’s social network, which leads to (self-)isolation and social distrust. Conclusion. PWE experience of social inclusion depends on various psychosocial factors and differs from person to person. The consequences of epilepsy are shown in PWE social contacts and their sense of social inclusion and autonomy.